Pengaruh Konten Instagram terhadap Minat Beli Konsumen Space Coffee Roastery Yogyakarta - Ronaldho Rachman Jonni; Puji Hariyanti (Program Studi Ilmu Komunikasi UII, 2021)
This study is to determine the effect of content on Instagram on consumer buying interest in Space Coffee Roastery Yogyakarta. Instagram content is various kinds of things that are shared by users via Instagram accounts. This type of research is survey research. The number of samples is 100 respondents. Data collection using a questionnaire with a Likert scale. Processing and data analysis using quantitative descriptive analysis and simple linear regression analysis, significance test of individual parameters (t test), simultaneous significance test (F test), analysis of the coefficient of determination (R ²). The results showed that the percentage based on the Instagram content variable was dominated by very attractive as many as 71 (71%). The percentage based on the purchase interest variable was dominated by very high as much as 76 (76%). The results of the t test get a result of 0.000 <0.05, it can be concluded that Instagram content has a significant effect on buying interest. This shows that the more often you attract Instagram content, the more consumer interest in buying Space Coffee Roastery Yogyakarta will increase.